Keputusan Amerika Serikat Menarik Pasukan Dari Jerman Tahun 2020 - Sudira, I Gede Bayu Wicaksana; Wiranata, I Made Anom; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
This research aims to qualitatively describe the reasons of the United States to withdraw their troops from Germany in 2019. Systemic pressure from NATO affects United States decision. The position and important role that America has in NATO did not prevent it from taking this decision. The researcher uses Neo Classical Classical Realism theory to see behind the decision to withdraw United States troops from Germany through two levels,  systemic and domestic. Domestically, researchers deepen the discussion through the concept of economic interest. The decision taken by the United States is an answer to the situation that occurs at the structural level by emphasizing the interests of the national economy.